2022
DOI: 10.1039/d2mh01070d
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the thermal conductivity of two-dimensional metal halide perovskites

Abstract: Proper thermal management of solar cells based on metal halide perovskites (MHPs) is key to increasing their efficiency as well as their durability. Although two-dimensional (2D) MHPs possess enhanced thermal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The thermal conductivities determined via k = D•c p •ρ and shown in Figure 2(d) also feature only minor temperature dependencies. In agreement with recent experimental and theoretical studies, 48,49,57 we observe that both RP materials have lower thermal conductivities than MAPbI 3 . Furthermore, the thermal conductivity of PEA 2 PbI 4 is lower than that of BA 2 PbI 4 .…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The thermal conductivities determined via k = D•c p •ρ and shown in Figure 2(d) also feature only minor temperature dependencies. In agreement with recent experimental and theoretical studies, 48,49,57 we observe that both RP materials have lower thermal conductivities than MAPbI 3 . Furthermore, the thermal conductivity of PEA 2 PbI 4 is lower than that of BA 2 PbI 4 .…”
Section: Resultssupporting
confidence: 92%
“…While the dynamic distortions markedly influence the free carrier masses and drift-diffusion transport mechanisms, they do not affect the exciton binding energies and exciton diffusion in quasi-2D RP perovskites . Thermal transport properties of quasi-2D RP perovskites have come into focus only recently, when several experimental and theoretical studies ,, reported ultralow thermal conductivities in A 2 PbX 4 (A = BA, PEA, X = I, Br) using thermal reflectance measurements combined with molecular dynamics simulations based on a classical force field. A theoretical study using a similar force field by Fridriksson et al also showed that length and aromaticity of the interlayer molecule significantly affect the structural rigidity of the perovskite sublattice .…”
Section: Introductionmentioning
confidence: 99%
“…Particularly remarkable is the case of K 3 ITe, as its κ L at room temperature is much lower than that of leading thermoelectric materials such as PbTe and Bi 2 Te 3 (with κ L values of ∼1 W m −1 K −1 ). Moreover, K 3 ITe stands out with a κ L value that is lower than those of currently popular metal halide perovskites, such as CsCdBr 3 (∼0.42 W m −1 K −1 ), 52 CsSrF 3 (∼0.90 W m −1 K −1 ), 51 and CsPbI 3 (∼0.56 W m −1 K −1 ), 53 antiperovskites such as K 3 BrO (∼1.7 W m −1 K −1 ) and Rb 3 BrO (∼0.8 W m −1 K −1 ), 54 and alloy materials. 55 To assess the temperature dependence of κ L , we fit the κ L with the relation κ L ∝ T −α .…”
Section: Chemistry Of Materialsmentioning
confidence: 87%
“…16 Similarly, the thermal conductivity of COFs can be effectively modulated through strain engineering. 17,18 Besides, mechanical stimuli are also inevitable in many applications of 2D materials. For instance, in the thermal catalysis applications of 2D materials, such as 2D MXenes, the operational conditions typically encompass elevated temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%